The Correlation of Utilization Facebook Social Networking Sites with the students’ Learning Outcomes of IAIN Bone - Rina Novianty (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This aim of this article was to determine the correlation between using Facebook social networking sites with student learning outcomes of IAIN Bone. The sample of this research was the students of the Faculty of Economics and Business Islam, with 120 students in random sampling technique. Data analysis techniques used descriptive data analysis and inferential data analysis. The results showed that there was no correlation in the use of social networking sites Facebook with student learning outcomes for IAIN Bone, where sig = 0.071 > 0.05 and r count = 0.166 < rtable = 0.176, which means that the null hypothesis (H0) was accepted and hypothesis alternative (H1) is rejected Keywords: Facebook as Learning, Learning Outcomes, Utilization Facebook in Learning